STM32-based IoT Monitoring System for an Indoor Plant - K. N, Khamil.; Y.Z, Khoo; A.N, Isa. (International Journal of Intelligent Systems and Applications in Engineering, 2022)
There was a rise in interest in the horticulture industry when the pandemic started. Gardening became pleasurable and calming activity. However, not everyone is born with a green thumb. Many of us lack understanding about plant care, such as how much water we need to water the plant and the best luminance for the plant. This project aims to develop a system with a soil moisture sensor used to calculate the indoor plant’s soil moisture percentage and a digital light intensity sensor applied to estimate the plant’s luminance need using STM32 based microcontroller. The soil moisture value and luminance will be shown on the sensor’s built-in OLED. All parameters will be sent to the user via a Wi-Fi connection established between the mobile phone and the ESP8266. As a result, the plant status was monitored using Blynk apps through the smartphone by the designated user. These promising results are presented as one of the main achievements of this work and help the plant community better monitor their plant health.